2016
DOI: 10.1007/s00221-015-4545-9
|View full text |Cite
|
Sign up to set email alerts
|

EEG frequency analysis of cortical brain activities induced by effect of light touch

Abstract: In human postural control, touching a fingertip to a stable object with a slight force (<1 N) reduces postural sway independent of mechanical support, which is referred to as the effect of light touch (LT effect). The LT effect is achieved by the spatial orientation according to haptic feedback acquired from an external spatial reference. However, the neural mechanism of the LT effect is incompletely understood. Therefore, the purpose of this study was to employ EEG frequency analysis to investigate the cortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 72 publications
1
21
0
4
Order By: Relevance
“…This could mean that the left IPG plays a role in the detection of multisensory conflict or the directing of tactile attention. This is in correspondence with reports by Ishigaki and colleagues [13], who suspected involvement of the left primary somatosensory and posterior parietal cortices in the processing and integration of steadystate right hand light touch. On the other hand, we disrupted the left and right PPC by cTBS and did not find any alterations in sway progression following removal of active light touch [10].…”
Section: Discussionsupporting
confidence: 92%
“…This could mean that the left IPG plays a role in the detection of multisensory conflict or the directing of tactile attention. This is in correspondence with reports by Ishigaki and colleagues [13], who suspected involvement of the left primary somatosensory and posterior parietal cortices in the processing and integration of steadystate right hand light touch. On the other hand, we disrupted the left and right PPC by cTBS and did not find any alterations in sway progression following removal of active light touch [10].…”
Section: Discussionsupporting
confidence: 92%
“…Ishigaki et al . (), however, did not report bilateral activity changes during quiet stance with light touch but exclusively in the dominant hemisphere contralateral to the contacting hand. As both hemispheres were undisturbed physiologically in their experiment, it may be that any ipsilateral activity changes in the right hemisphere were suppressed.…”
Section: Discussionmentioning
confidence: 69%
“…Ishigaki et al . () demonstrated that processing of a haptic signal when it contains information about body sway relative to an earth‐fixed reference reduces cortical activity in the contralateral left‐hemisphere parietal lobe as determined by EEG. Unfortunately, they did not assess the effect of contact with the non‐dominant (left) hand.…”
Section: Discussionmentioning
confidence: 99%
“…EEG data were band-pass filtered in the range of 0.1–50.0 Hz and applied to a common average reference montage. We removed artifacts using previously described methods 24,25. Briefly, artifacts generated by blinking, eye movements, facial muscle activity, or body movements were removed using a specially designed spatial filter in EMSE Suite 5.4 and visual inspection of the frontal EEG trace (Fp1, Fp2).…”
Section: Methodsmentioning
confidence: 99%